Telaah Leksikal, Gramatikal, dan Kontekstual Terhadap Makna Kata Syahida pada QS. al-Baqarah ayat 185 - Budi Kisworo; H Hardivizon (AL QUDS : Jurnal Studi Alquran dan Hadis, 2020)
This writing contains a semantic study of surah Al-Baqarah verse 185.As it is known, fasting is explained by Allah SWT through surah Al-Baqarah verse 183-185.In the verse 183, Allah explains the obligation of fasting for the believers; the verse 184 contains an explanation of the days in which the obligation of fasting must be fulfilled; and the verse 185 implies the way to know the coming of the month of Ramadan as a month in which fasting is obligated.The mufassirins understand the verse 185 of Al-baqarah asinformation about the condition of someone who presents (meets) the month of Ramadan, then it is obligatory upon him to fast.This understanding departs from the word "shahida" which means "present" or "be" (in the country of residence). The writer conducted a lexical, grammatical, and contextual research of the meanings included in the "shahida" lafaz, where the meaning of "witnessing" or "knowing" also falls within the scope of the shahida meaning, and that meaning is felt to be more in line with maqashid shari'ah.Witnessing and knowing the coming of the month of Ramadan is the condition of someone who gains knowledge and beliefthat the month of Ramadan has come. Those knowledge and belief can be obtained through rukyat (the physical sighting of the moon) or hisab (calculation). However, because the word "shahida" is related to the word "shahr", it is not appropriate if the method used is rukyat because "shahr" means month in terms of numbers, not months in terms of objects.Therefore, in this context, the right way is hisab (calculation) because hisab is a method / way of knowing the coming of the month of Ramadan with numbers / counting.Thus, the cue given by Allah in the verse 185 of Al-Baqarah is an order to know the coming of Ramadan by doing hisab (calculation)